On the evolution of power indices in collective bargaining - Siegfried Berninghaus; Werner Güth (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
Starting point of our (indirect) evolutionary analysis is the sequential bargaining model of Manning (1987) who distinguishes between trade union's power in initial wage and in later employment negotiations. By linking two such collective bargaining situations we can say which of the two (two-dimensional) power constellations is better and thereby derive the power structure endogenously. By distinguishing various measures of (evolutionary or reproductive) success we can identify the forces shaping the relative power indices of trade unions.
urn:nbn:de:kobv:11-10048354
Keywords: 330